The Mughal state, 1526-1750 - Alam, Muzaffar, 1947-; Subrahmanyam, Sanjay (Delhi ; New York : Oxford University Press, 1998)
Contributed articles.
Includes bibliographical references (p. [520]-536).
Keywords: Mogul Empire -- History